Prevalence of self-reported mental disorders in pregnancy and associations with adverse neonatal outcomes: a population-based cross-sectional study - David Mongan; Janine Lynch; Donncha Hanna; Ciaran Shannon; Shona Hamilton; Claire Potter; Colin Gorman; Orlagh McCambridge; Rachel Morrow; Ciaran Mulholland (BMC, 2019)
Abstract Background Mental disorders in pregnancy are common causes of morbidity and mortality with associated risks of adverse neonatal outcomes. Our aims were to evaluate the prevalence of self-reported mental disorders in women presenting to maternity services and to determine the association between history of self-reported maternal mental disorder and adverse neonatal outcomes. Methods Data on all singleton pregnancies known to maternity services in Northern Ireland over the period 2010 to 2015 were extracted from the Northern Ireland Maternity System (NIMATS), including frequency data for number of pregnancies where the mother reported a history of mental disorder. Odds ratios were derived from logistic regression analyses to determine the associations between self-reported maternal mental disorder and preterm birth, low infant birth weight and APGAR scores. Results In total, 140,569 singleton pregnancies were registered using NIMATS over this period. In 18.9% of these pregnancies, the mother reported a history of at least one mental disorder. After adjustment for potential confounding factors, significant associations were demonstrated between self-reported maternal mental disorder and preterm birth (odds ratio [OR] 1.31, 95% confidence interval [CI] 1.25-1.37), low infant birth weight (OR 1.29, 95% CI 1.21-1.38) and APGAR score < 7 at 1 min (OR 1.14, 95% CI 1.10-1.19) and 5 min (OR 1.23, 95% CI 1.12 to 1.34). Conclusions These findings emphasise the critical importance of routine enquiry regarding psychiatric history when women present to maternity services and the impact of maternal mental illnesses upon outcomes for their infants.